Synthesis and Experimental Validation of New Designed Heterocyclic Compounds with Antiproliferative Activity versus Breast Cancer Cell Lines MCF-7 and MDA-MB-231. (2nd April 2017) - Barresi, Vincenza; Bonaccorso, Carmela; Cristaldi, Domenico A.; Modica, Maria N.; Musso, Nicolò; Pittalà, Valeria; Salerno, Loredana; Fortuna, Cosimo G.
Abstract : Recent drug discovery efforts are highly focused towards identification, design, and synthesis of small molecules as anticancer agents. With this aim, we recently designed and synthesized novel compounds with high efficacy and specificity for the treatment of breast tumors. Based on the obtained results, we constructed a Volsurf+ (VS+) model using a dataset of 59 compounds able to predict the in vitro antitumor activity against MCF-7 cancer cell line for new derivatives. In the present paper, in order to further verify the robustness of this model, we report the results of the projection of more than 150 known molecules and 9 newly synthesized compounds. We predict their activity versus MCF-7 cell line and experimentally verify the in silico results for some promising chosen molecules in two human breast cell lines, MCF-7 and MDA-MB-231.